2014
DOI: 10.1016/j.virol.2014.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegypti salivary protein “aegyptin” co-inoculation modulates dengue virus infection in the vertebrate host

Abstract: Dengue virus (DENV) is transmitted in the saliva of the mosquito vector Aedes aegypti during blood meal acquisition. This saliva is composed of numerous proteins with the capacity to disrupt hemostasis or modulate the vertebrate immune response. One such protein, termed “aegyptin,” is an allergen and inhibitor of clot formation, and has been found in decreased abundance in the saliva of DENV-infected mosquitoes. To examine the influence of aegyptin on DENV infection of the vertebrate, we inoculated IRF-3/7 −/−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 53 publications
(55 reference statements)
0
35
0
Order By: Relevance
“…Hematophagous arthropod saliva can also enhance transmission of arboviruses, although the exact mechanism and saliva proteins involved in this process are not known [ 3 ]. Interestingly, individual saliva components can have inhibitory activities that prevent arbovirus infection [ 19 ]. Here, we identified D7 protein in biochemical fractions of salivary gland extracts that inhibited DENV2 cell binding and/or infection in mouse embryonic fibroblasts and then determined if this activity could be recapitulated with recombinant D7 protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematophagous arthropod saliva can also enhance transmission of arboviruses, although the exact mechanism and saliva proteins involved in this process are not known [ 3 ]. Interestingly, individual saliva components can have inhibitory activities that prevent arbovirus infection [ 19 ]. Here, we identified D7 protein in biochemical fractions of salivary gland extracts that inhibited DENV2 cell binding and/or infection in mouse embryonic fibroblasts and then determined if this activity could be recapitulated with recombinant D7 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, individual saliva components can have inhibitory activities against arbovirus infection. For instance, the collagen-binding protein aegyptin decreased DENV infection in vivo [ 19 ]. Additionally, previous literature showed that vaccination of mice with a recombinant D7 protein from Culex spp .…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] The effects of MSP on mosquito-borne viral infections have been reviewed previously, and include 1) alterations to vascular permeability in DENV infection, 2) changes in cytokine and innate signaling profiles, such as decreased expression of IFNβ/γ, IL-2, and TLR3/7 and increased expression of IL-4, IL-10, and IL-12 in DENV, Chikungunya virus (CHIKV), and West Nile virus (WNV) infections, and 3) migration of monocytes, neutrophils, eosinophils, and plasma cells to the site of infection for DENV, CHIKV, and WNV, as well as increased WNV neurovirulence. [38,[40][41][42][43][44][45][46][47] Additionally, Aedes aegypti MSP increased the prevalence of disease signs and extended the viremic period in DENV-infected, humanized mice. [48] Various methods have been utilized to incorporate MSP into arbovirus research, including salivary gland extract (SGE) and feeding by infectious mosquitoes.…”
Section: Introductionmentioning
confidence: 99%
“…The virus passes from the mosquito intestinal tract to the salivary glands after an extrinsic incubation period, a process that takes approximately 10 days, which may vary depending on the ambient temperatures[ 14 ]. Mosquito bites after the extrinsic incubation period result in infection, which might be promoted by mosquito salivary proteins[ 15 17 ]. The abundance of dengue vector as well as dengue transmission generally exhibits seasonal variation depending on the local ecology and urban environment.…”
Section: Introductionmentioning
confidence: 99%